Relationship Between Mixed Chimerism and Acceptance of HLA-matched and -Mismatched Kidney Transplants after Withdrawal of Immunosuppressive Drugs. (July 2018) - Busque, Stephan; Scandling, John; Lowsky, Robert; Shizuru, Judith; Jensen, Kent; Shori, Asha; Hoppe, Richard; Engleman, Ed; Meyer, Everett; Strober, Samuel
Abstract : Classical studies in cattle and rodents showed that mixed chimerism established in fetuses and neonates was permanent, and was linked to immune tolerance and the acceptance of organ grafts from the hematopoietic cell donors without need for immunosuppressive (IS) drugs. The goal of the current clinical study was to determine whether establishment of persistent mixed chimerism for at least 1 year in HLA-matched and -mismatched recipients of combined kidney and hematopoietic cell transplants from living donors followed the preclinical paradigm and allowed for permanent chimerism and acceptance of transplant kidneys in the absence of IS drugs. Recipients were given a 10-day post-transplant conditioning regimen of total lymphoid irradiation and rabbit anti-thymocyte globulin. Of 29 HLA-matched patients, 24 developed mixed chimerism for at least 1 yr and were completely withdrawn from IS drugs from mo 6 through 18. There was no subsequent rejection in 23 of the 24, with up to 12 yrs of follow-up. Mixed chimerism persisted after drug withdrawal in 10, as in the preclinical studies. However, 14 had a pattern that differed from the paradigm and accepted the organ grafts after drug withdrawal despite loss of chimerism during the 2nd yr. Pts with long-term graft acceptance off drug had specific unresponsiveness to donor allo-antigens in the MLR even in the absence of stable mixed chimerism. There were 2 graft losses among the 29 during the 12-yr observation period due to return of underlying kidney disease. Biopsies obtained from mixed chimeric pts just before discontinuation of IS drugs showed no rejection. Of 22 HLA haplotype-mismatched patients, 18 have been followed for more than 1 yr, and 9 developed mixed chimerism that persisted at least 1 yr. MMF was withdrawn from the chimeric pts such that they were maintained on tacrolimus (TAC) monotherapy at the end of the 1st yr, and biopsies showed no rejection at this time. However, withdrawal of TAC in 6 during the 2nd yr resulted in loss of mixed chimerism with evidence of mild rejection in 3; they returned to IS drugs. Mixed chimerism in these HLA-mismatched pts did not follow the "classical" paradigm - it was unstable and dependent on IS drugs. The remaining persistent chimeras have been maintained on TAC monotherapy. There has been no graft loss or chronic rejection in the 22 pts, with up to 7 yrs of follow-up. Neither severe or chronic infection, nor graft versus host disease, has been observed in the HLA-matched and -mismatched pts. In conclusion, persistent mixed chimerism protected against rejection in both HLA-matched and -mismatched patients. Whereas long-term acceptance of kidney transplants off IS drugs was observed even after loss of chimerism in HLA-matched pts, protection against rejection was associated with persistence of mixed chimerism in HLA-mismatched pts. The latter outcome in HLA-mismatched pts is desirable if chimerism can be maintained on low-dose TAC monotherapy.